Evaluation of bimodal microstructures in selective-laser-melted and heat-treated Ti-6Al-4V. (March 2023) - McKenna, Tom; Tomonto, Charles; Duggan, Greg; Lalor, Eoin; O'Shaughnessy, Seamus; Trimble, Daniel
Graphical abstract: Highlights: The response of SLM Ti64 to 'cyclical' heat treatment strategies was characterised in terms of microstructure and mechanical performance The number of thermal cycles experienced in a 'cyclical' profile heat treatment significantly influences the high-cycle fatigue behaviour A lamellar microstructure was shown to out-perform a bimodal microstructurein both tensile and high-cycle fatigue testing. Abstract: As-built, SLM-printed Ti-6Al-4V parts suffer from non-equilibrium, brittle microstructures due to the formation of metastable α'-phase martensite as a result of the printing process. Post-processing heat treatments are required to alleviate residual stress and decompose the martensite into equilibrium phases. Using unconventional 'cyclical' heat treatment profiles, it is possible to achieve a bimodal microstructure as opposed to a more typical lamellar microstructure achieved using conventional heat treatment profiles. In the present research, the effect of cyclical heat treatment parameters (maximum temperature, minimum temperature, number of cycles and cooling regime) on the grain morphology, phase composition and mechanical performance (static and dynamic) has been evaluated. Furthermore, a comparison to a typical lamellar microstructure has been completed as a reference.